(untitled) (Journal of Environmental Science and Natural Resources, 2013)
An attempt is made to investigate the trend and variability for annual and seasonal (Three crop seasons) average maximum temperature (AMXT) for six divisional stations of Bangladesh: Dhaka, Rajshahi, Khulna, Barisal, Sylhet and Chittagong. The monthly AMXT (2009-2012) are forecasted applying univariate Box-Jenkins ARIMA (autoregressive integrated moving average) modeling techniques. The growth rates of annual AMXT are found positive in all the stations except Rajshahi (negative) while the rates of their coefficient of variations (CVs) are negative in all the stations except Khulna (negative). The rates of AMXT are positive during Kharif season but negative in Prekharif and Rabi seasons for Rajshahi and Khulna, positive during Kharif and Rabi season but negative in Prekharif season for Dhaka and Barisal and positive in all the three seasons for Sylhet and Chittagong. The findings support that the climate of this country is channging in terms of maximum temperature and this may have adverse effects on its agriculture. DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14803 J. Environ. Sci. & Natural Resources, 5(2): 119-128 2012